Exploring Inflammatory Changes in the Peripheral Blood of Type 2 Diabetes Mellitus in China - Li D; Zhang Z; Li W; Zhao C; Li X; Pan Z; Li Y (Journal of Inflammation Research)
Dan Li,1,2,* Zhiru Zhang,3,* Wen Li,2 Chenhao Zhao,2 Xiaochen Li,2 Zhen Pan,2 Yang Li1 1Department of Clinical Laboratory, Children’s Hospital of Soochow University, Suzhou, Jiangsu, 215025, People’s Republic of China; 2Department of Clinical Laboratory, the Second Affiliated Hospital of Soochow University, Suzhou, Jiangsu, 215004, People’s Republic of China; 3Department of Human Resources, the Affiliated Hospital of Nantong University, Nantong, Jiangsu, 22600, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yang Li, Department of Clinical Laboratory, Children’s Hospital of Soochow University, Suzhou, Jiangsu, 215025, People’s Republic of China, Tel +86-512-80691230, Email 11418092@zju.edu.cnObjective: Type 2 diabetes mellitus (T2DM) is a serious, chronic metabolic disease globally and its pathogenesis is not completely understood yet. This study aimed to thoroughly investigate the fluctuation of inflammatory markers in the peripheral blood of patients with T2DM, which are rarely reported.Methods: Peripheral blood samples from patients with T2DM and healthy individuals, as well as their clinical information, were collected at the Second Affiliated Hospital of Soochow University. Flow cytometry was used to analyse the immune cells and cytokines in the peripheral blood. CCK-8 assay was performed to detect the viability of THP-1 cell after treatment with 5 m&Mgr; or 50 m&Mgr; glucose. Flow cytometry, Western Blotting and qPCR were used to analyse the apoptosis of monocytes or THP-1 cells.Results: The numbers of white blood cells, lymphocytes, and neutrophils substantially increased with elevated IL-6 levels. There was a significant decrease in monocytes due to increased cell apoptosis caused by sustained high glucose stimulation. Hyperglycemia reduced monocyte viability and altered monocyte subgroups by increasing the number of intermediate and non-classical monocytes.Conclusion: In summary, our work reveals that patients with T2DM do have variations of peripheral inflammation biomarkers, especially monocytes.Keywords: Type 2 diabetes mellitus, peripheral inflammation, monocytes